Foreign direct investment and China's bilateral intra-industry trade with Japan and the US - Yuqing Xing (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper analyzes dynamic changes of China's intra-industry trade with its major trading partners, Japan and the US, from 1980 to 2004.It also investigates to what extent foreign direct investment promoted intra-industry trade.The empirical results show that, while shares of China's intra-industry trade with both Japan and U.S rose substantially, its intraindustry trade with Japan has reached 35 per cent of the overall trade, considerably larger than 10 per cent with the US.Sino-Japan intra-industry trade concentrated in the electrical and machinery sectors accounted for 52 per cent and 46 per cent of overall trade respectively.On the other hand, it is in the chemical and food sectors where intra-industry trade represented a relatively large proportion of Sino-US trade, 50 per cent and 30 per cent accordingly in each sector.In addition, the analysis indicates that Japanese direct investment in China performed a significant role in enhancing intra-industry trade between Japan and China.However, it found no evidence that the US direct investment in China contributed to the growth of the bilateral intra-industry trade between the two countries.
URN:NBN:fi:bof-201408072059
Keywords: F14; F23; 330; Intra-industry trade; FDI; China